ANALISIS TINGKAT KERAWANAN KOTA PADANG DALAM MENGHADAPI BENCANA GEMPA BUMI - Rima Fadhilla Ulfa; Iswandi U (JURNAL BUANA, 2020)
This study purposed for know about : (1) the level of vulnerability of Padang City to earthquake disaster, and (2) the appropriate mitigation directions in according to this research. The type of data is secondary data from The Central Statistic Agency of Padang City, The Padang City Regional Disaster Management Agency, and The Padang City Social Service. Based on this research the conclusion is : (1) the level of vulnerability of Padang City influenced by population density where areas with high vulnerability are the district of Koto Tangah, Nanggalo, Kuranji, Padang Selatan, Padang Utara, Padang Barat, Padang Timur, and LubukBegalung, and (2) the right mitigation is to focus on areas with hight level of vulnerability and capacity then provide education to the public about earthquake mitigation and through media so people can save themselves without waiting for Government and related agencies assistance.